Association analysis of TGFBR3 gene with Behçet's disease and idiopathic intermediate uveitis in a Caucasian population. Issue 5 (12th February 2015) - Barry, Robert J; Alsalem, Jawaher A; Faassen, Juliet; Murray, Philip I; Curnow, S John; Wallace, Graham R
Abstract : Background: Transforming growth factor β (TGFβ) is an important immunoregulatory cytokine in regulatory T cell (Treg) and Th17-mediated pathology, including uveitis due to Behçet's disease (BD). Of the three isoforms, TGFβ2 is found at highest levels in the aqueous humour of uninflamed eyes. TGFβ signals through a cell-surface receptor comprising three subunits (TGFBR1, 2 and 3). TGFBR3 is considered necessary for TGFβ2 signal transduction, but not for other isoforms. A polymorphism in TGFBR3 (rs1805110) has previously been identified in Han Chinese patients with BD. We investigated the frequency of this polymorphism in a Caucasian population with BD and idiopathic intermediate uveitis (IIU). Methods: The single-nucleotide polymorphism (SNP) rs1805110 in TGFBR3 was genotyped in 75 BD patients, 92 IIU disease controls and 85 disease-free controls. The association with both diseases was analysed using Fisher's exact test. Results: No significant difference in rs1805110 allele or genotype frequency was observed. A low frequency of the T allele was observed (5.88% control, 9.33% BD, 10.33% IIU) with the TT genotype absent in patients with BD and IIU (1.18% control, 0% BD and 0% IIU). Stratification analysis according to clinical features of BD did not associate with the tested SNP. Conclusions: RS1805110 is not associated with BD or IIU in Caucasian patients. The T allele frequency is consistent with that presented for Caucasian populations in the HapMap database (p>0.05). Our results differ from the previous analysis in Han Chinese patients (p<0.0001), however, the possibility of having a much smaller effect due to the low minority frequency cannot be excluded.